Analysis Of Parenting Style On Child Development At The Age 3-5 Years - Aprillia Ayu Shinta Yuka; Yunetra Franciska (Poltekkes Kemenkes Palembang, 2022)
Background: The development stimulation and developmental abnormalities of children are discussed today as more and more cases are finds are found in all groups. Unfortunately, the cases were found late. The development is influenced by internal factors that include genetic and hormonal, including environment, as an external factor, especially parents stimulation. Parents stimulation included the meet of physical and psychological needs of their children, through nutrition and good parenting style. Purpose: This study aims to determine the effects of nutrition and parenting style on children development age 3-5 years in Wilayah Puskesmas Sosial District of Palembang. Methods: The analytic survey research with cross sectional design and Binary Logistic Regression was conducted in 10 PAUD / TK located in the area of ​​Puskesmas Sosial Palembang from September to November 2016. The samples were 107 children aged 3 -5 years taken with purposive sampling technique using Simple Random Sampling method. Data were analysed using SPSS version 16.0. Results The result of the analysis shows that there was an influence of parenting style toward child development (p value = 0.000). Multivariate analysis showed that parenting style has an influence on the development of children by 70%, while 30% influenced by other factors. The conclusion of this study were the non-authoritative parenting style will lead to the doubting development of child 6 times greater than the authoritative parenting style.